Love in four Central American short stories - Martínez Alpízar, Diana (2023)
The present article analyzes the love in four short stories written by Central American female writers: Jessica Clark, María del Carmen Pérez Cuadra, Jennifer Rebecca Valiente y Denisse Phé-Funchal. These writers started to publish at the begging of 21th century; by contrast, the academic production about them is still raising. For that reason, it is necessary to pay attention to these voices that, little by little, step up in Central American literature. With that aim, the present article focus in how are the love and topics related with it (like family or marriage) (re)formulated. After a theorization about love and its transformations in the History, it presents a brief contextualization about the present in Central American Literature and a state of the art about the critical reception of the writers. Lastly, the article presents the analyzes of each short stories, based on several tool provided by structuralism (like narrator voice, characters, narrative levels) and by semiotic. It concludes that in the short history the characters detach from romantic love, because it is dangerous, or it is impossible to achieve. In other cases, the characters that are committed with the search of romantic love ended in tragic ways.